Respon Perkecambahan Benih Asam Jawa (Tamarindus Indica) Terhadap Berbagai Konsentrasi Larutan Kalium Nitrat (Kno3) - Elfri Mentari Situmorang; Melya Riniarti; Duryat Duryat (Jurnal Sylva Lestari, 2015)
Tamarind (Tamarindus indica) is a multipurpose tree that can be developed either vegetative or generative propagation. Vegetative propagation of tamarind can produce abundant fruit if the plant organs derived from superior parent trees. However, due to the rare availability of natural tamarind stands now days, then the generative propagation by seed, can be the right choice for its cultivation. Generally, tamarind seeds are dormant, so it requires a pre-treatment to break its dormancy. One way to break it was using potassium nitrate (KNO3). This study aimed to determined the response of soaking treatment to the germination of tamarinds seeds with KNO3 solution at various concentrations and the most effective concentration of KNO3 solution to stimulate tamarind seeds germination. The experiment was conducted at the Greenhouse Seed Control and Certification Institute of Food Crops and Horticulture (BPSBTPH) Lampung Province, from July to August 2013. This research used Completely Randomized Design (CRD), with 5 treatment of KNO3 solution soaking (0.1%, 0.2%, 0.3%, 0.4% and without KNO3) and 3 replications. Every unit of experiments consisted of 100 seeds. Observed parameters included percentage of germination, mean of day germination and percentage of germination seeds per day. Bartlett test was employed to figure out the homogenity of datas. Then, analysis of variance was used to analyse datas. Honestly Significant Difference (HSD) was used to the advanced analysis. The entire data tested on 5% significant level. The result showed that soaking of tamarind seeds in water (without KNO3) during 24 hours gave the best response to break its dormancy, and the most effective concentration to break dormancy of tamarind seeds was 0.4%. Keywords: dormancy, germination, pottasium nitrate, tamarind